The handbook of equity market anomalies translating market inefficiencies into effective investment strategies - Zacks, Len (Wiley finance series., 2011)
"The Zacks Handbook of Investment Anomalies will be the definitive work that presents and updates academic and practitioner research on market inefficiencies that can be translated into effective investment strategies. Edited by Len Zacks, a CEO of Zacks Investment Research, the book will explore earnings revisions and surprises; trading by company insiders; stock price momentum patterns; low price-earnings ratios; sector characteristics; seasonal patterns and other areas or market inefficiencies. The goal will be to present historical research on definable situations where particular stocks outperform the overall market. The insights from the research can then be utilized to construct a market-beating strategy going forward. While many of the chapters will be written by academics, an effort will be made to make the articles engaging and interesting to investment practitioners. The initial table of contents might be something like: Theoretical Framework within which to discuss market inefficiencies -- EPS Surprises- trading around EPS announcement dates -- Estimate Revisions - the oldest anomaly -- Insider Trading - it works if you clean the data -- Balance Sheet Accruals - longer term profits -- Price Momentum - 50 ways to measure it , do any work ? -- Low PE - when , why, and does it work -- Best Anomalies in each Sector - what works in each Sector -- Academically sound Technical Analysis - it's a new world -- Calendar based anomalies - do they exist ,can you make money using them -- Anomalies in Non US Markets ( 1 to 10 outside the US ) -- Selecting Mutual Funds -can you predict manager performance -- High Frequency trading anomalies - got a second?"--